(untitled) (Research, Society and Development, 2022)
The present study aims to raise and summarize how metric concepts are structured by hierarchical ontology and also classified by mathematics to finally be represented by a decision support tool. This is a narrative literature review carried out in international databases and gray literature. Thematic content analysis was used with the application of its stages in the material, from which two categories emerged a posteriori; hierarchical ontologies: description of objects through structures and categorization of mathematically structured concepts. It was found that ontology is responsible for the process of sharing, defining, conceptualizing and structuring concepts, the representation theory of mathematics has the task of developing conceptuais systems to define properties/attributes to guarantee the extension and identity of an object and knowledge management organizes knowledge from previous disciplines on machines, saving time and reducing effort. Therefore, until nursing administration manages to make assessment models available in the context of practice for use in statistical tests, there is a long scientific path.